2003
DOI: 10.1097/01.pcc.0000074273.50306.f5
|View full text |Cite
|
Sign up to set email alerts
|

Massive diltiazem overdose treated with extracorporeal membrane oxygenation

Abstract: Although massive calcium channel blocker overdose can produce profound and prolonged cardiac or multiorgan dysfunction, its toxic effects may be reversible. Supportive therapy, particularly of the cardiovascular system, is the most important goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 19 publications
1
42
0
1
Order By: Relevance
“…These early studies showed improved mortality in models of lidocaine and amitriptyline poisoning [11,12]. Numerous human case reports and case series have since shown favorable outcomes although ECMO has been primarily used in poisonings involving pharmaceuticals such as antidysrhythmics and other cardiovascular medications, as well as tricyclic antidepressants [13][14][15][16][17][18][19][20][21][22][23][24][25]. Many of the pharmaceutical exposures in our cohort were similar to cases reported in the literature with most leading to cardiotoxicity or hemodynamic collapse (flecainide, diphenhydramine, and verapamil).…”
Section: Discussionmentioning
confidence: 99%
“…These early studies showed improved mortality in models of lidocaine and amitriptyline poisoning [11,12]. Numerous human case reports and case series have since shown favorable outcomes although ECMO has been primarily used in poisonings involving pharmaceuticals such as antidysrhythmics and other cardiovascular medications, as well as tricyclic antidepressants [13][14][15][16][17][18][19][20][21][22][23][24][25]. Many of the pharmaceutical exposures in our cohort were similar to cases reported in the literature with most leading to cardiotoxicity or hemodynamic collapse (flecainide, diphenhydramine, and verapamil).…”
Section: Discussionmentioning
confidence: 99%
“…Because the treatment protocol for calcium channel blocker intoxication is supported by low-quality evidence, the treatment regimen is determined according to the severity of symptoms, including high-dose insulin, intravenous calcium gluconate injection, intravenous glucagon injection, intravenous vasopressor infusion and lipid emulsion therapy (5). Furthermore, it has been reported that extracorporeal life support is associated with a survival benefit in the setting of multiorgan dysfunction, severe shock and/or cardiac arrest after diltiazem overdose (5,(10)(11)(12). Although our patient was managed conservatively, his clinical course was uneventful and the serum diltiazem concentration decreased on day 3 (35.9 ng/mL).…”
Section: Discussionmentioning
confidence: 89%
“…La paciente del caso reportado con intoxicación intencional por amlodipino, cursó con choque vasodilatado y disfunción multiorgánica, acidosis metabólica, azoemia, edema pulmonar no cardiogenico, sin evidencia de bradiarritmia y depresión miocárdica, cuadro clínico y hemodinámico similar a los reportados previamente (6)(7)(8). El manejo incluyó soporte con ventilación mecánica, solución salina 0,9%, vasopresores múltiples a dosis por encima de las habituales para lograr estabilidad, gluconato de calcio, bicarbonato de sodio, dextrosa 10% con insulina regular (3,5,(7)(8)(9); no se usó glucagón por no tener disponibilidad.…”
Section: Discussionunclassified